The influence of green products on green purchase intention mediated by green brand awareness - Diyah Winarni, Roro Suestu (International Journal of Applied Finance and Business Studies, 2024)
Consumer behavior has shifted to concern for the environment. Creating green products has become a big agenda for every entrepreneur, and they must continue to follow global changes. This study aims to analyze how green products can affect green purchase intention mediated by green brand awareness. This study uses quantitative methods to determine the relationship between variables. The sample used in this study was 120 respondents. Questionnaires were used for data collection and analysis using SmartPLS software version 3. The analysis results confirm that green products can positively and significantly affect green purchase intention and partial green brand awareness. Green brand awareness can also affect green purchase intention positively and significantly. At the same time, green brand awareness can mediate the relationship between green products and green purchase intention positively and significantly